Pharmaceutical Quality Control Testing of Different Brands of Aspirin Sold in AL-Bayda City Markets - Yasmeen Amrajaa; Sara Gadalmwla; Almontaser Alashiby; Najat Farhat (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. The research studied official and unofficial quality tests to evaluate the quality of randomly selected brands of aspirin tablets that are sold in Bayda City. Six different brands of aspirin tablets (75, 100 mg) were randomly selected from retail pharmacies. Methods. Quality control tests, which included physical appearance, weight variation, hardness, friability, disintegration, and drug content tests, were carried out on the samples. All brands were checked visually to see if there were any manufacturing errors. The manufacturing defects include shape, size, and packaging. Results. The physical appearance of different aspirin tablets was free from all physical defects. Six different brands of aspirin tablets passed the test of weight variation. The weight variation percentage range was between -7.182% and 7.441%. The average hardness of all brands ranged from 47 to 121 N. The lowest one was ASA2 (47N), and the highest one was ASA3 (121N). The hardness of the tablets was found to be within the acceptable limits, except for the brand ASA3, which is far from the limit. The friability values for aspirin tablet brands ranged from 0.01 to 0.65%. All sex brands of aspirin have passed the friability test and have met the specifications of USP and BP pharmacopeias. The disintegration time for all aspirin tablets was within the pharmacopeial limits of 30 minutes. The drug content assay indicated that the aspirin tables were within the pharmacopeial limits. The content of aspirin presents in the various brands of commercial aspirin tablets with the codes ASA1 through ASA6 contained aspirin in amounts between 95.9 and 102 %. Conclusion. Good quality control involves testing units and determining if the aspirin tablets are within the specifications for the final products. Good quality control helps companies meet consumer demand for better products.